Health geography and the 'performative' turn: making space for the audio-visual in ethnographic health research. (November 2019) - Kaley, Alexandra; Hatton, Chris; Milligan, Christine
Abstract: The purpose of this paper is to critically reflect on the added value of video in ethnographic research that seeks to understand peoples' lived experiences of health and place. Of particular interest is the potential for video to elicit the embodied, multisensory and relational nature of people's place experiences that are the focus of much recent health geography research. We draw on our experiences of using video in an ethnographic study that sought to explore the experiences of people with intellectual disabilities engaged in nature based (or 'green care') therapeutic interventions for health and wellbeing. We argue that video has the potential to capture aspects of people's wellbeing experiences that may be lost using other methods, such as observational field noting. Consideration is also given to how researchers using video methods should seek to (re)present people's wellbeing experiences, as well as the practical and ethical challenges that this approach has for those working in the field of health geography. Highlights: This paper critically reflects on the added value of video method for health geography research. Video has the potential to present to the viewer certain affective encounters that are relevant for health. The use of video in health geography research raises some important ethical and practical challenges, which are discussed.